High‐Throughput Step Emulsification for the Production of Functional Materials Using a Glass Microfluidic Device. Issue 2 (14th December 2016) - Ofner, Alessandro; Moore, David G.; Rühs, Patrick A.; Schwendimann, Pascal; Eggersdorfer, Maximilian; Amstad, Esther; Weitz, David A.; Studart, André R.
Abstract : High‐volume production of monodisperse droplets is of importance for industrial applications due to increased emulsion stability, precise control over droplet volumes, and the formation of periodic arranged structures. So far, parallelized microfluidic devices are limited by either their complicated channel geometry or by their chemically or thermally unstable embedding material. This study shows a scalable microfluidic step emulsification chip that enables production of monodisperse emulsions at a throughput of up to 25 mL h −1 in a glass device with 364 linearly parallelized droplet makers. The chemical and thermal stability of such a glass device allows for the preparation of a broad variety of functional particles and microdroplets by using any desired solvent together with nanoparticles, polymers, and hydrogels. Moreover, the microfluidic device can be stringently cleaned for nearly unlimited use and permits the alternating production of oil‐in‐water and water‐in‐oil emulsions. The combined high throughput, chemical and thermal stability offered by our device enables production of monodisperse functional materials for large‐scale applications. Abstract : High‐throughput production of monodisperse emulsions is attractive in material‐, food‐, and pharmaceutical sciences, since it provides precise control to create functional microcapsules and microparticles. This study combines the scalability of step emulsification with the chemical inertness of glass devices to enable the robust and high‐volume production of a broad variety of functional materials.